PREMIX SUPPLEMENTATION IN FEED ON THE REPRODUCTIVE PERFORMANCE OF LANDRACE CROSSINGS WITH DUROC - N. S., Yosua; SUMARDANI, N. L. G.; SUMADI, I. K. (Majalah Ilmiah Peternakan; Vol 27 No 1 (2024): Vol. 27 No. 1 (2024)DO - 10.24843/MIP.2024.V27.i01.p08, 2024)
This research aims to determine the increase in reproductive performance of Landrace and Duroc cross sows given additional premix feed. This research was carried out in Br. Belong, Taro Kaja Village, Tegalalang District, Gianyar Regency, Bali Province. The crossbreed pigs used are Landrace and Duroc, 2-3 years old, or sows who have given birth 2-3 times. The experimental design used in this research was a completely Randomized Design (CRD) which consisted of 3 treatments, namely T0 feed without premix, T1 feed with premix and given to sows starting at 2 month of gestation, and T2 feed with premix and given to sows starting at 3 months of gestation. The average gestation period for the sow is 114 days and the premix dose is 1 kg/ 200 kg of feed. The results showed that the lit- ter size, birth weight, weaning weight, number of piglets weaned, and age at weaning showed significantly different results (P<0.05) in each treatment. Meanwhile, after weaning the sows re-mated, the results were not significantly different (P>0.05). The sow’s ability to maintain the litter size until weaning is very dependent on the quality of the feed given to the gestation of sow, especially feed that supports the sow’s milk production. From the results of this research, it can be concluded that giving premix to sows at 2-3 months of gestation (T2 and T3) can improve the reproduction performance of sows.